PERLAKUAN AKUNTANSI ATAS PEMBIAYAAN GADAI SYARIAH (AR-RAHN) PADA PT. BANK SYARIAH MANDIRI, TBK. CABANG PONTIANAK - B41110127, Muda Noviasri Pratama muda (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
PERLAKUAN AKUNTANSI ATAS PEMBIAYAAN GADAI SYARIAH (AR-RAHN) PADA PT. BANK SYARIAH MANDIRI, TBK. CABANG PONTIANAKMUDA NOVIASRI PRATAMAABSTRACTIn general terms the pawn business is the lending activities of valuables to a particular party, in order to earn some money and goods as collateral will be redeemed in accordance with the agreement between the customer and the institution pledge.The growing public interest about gadai syariah financing, the Islamic banking is one of the institutions that provide the product still must be guarded so that no banker irregularities against the existing system.This study purpose  to analyze the application of Standar Akuntansi Keuangan (SAK) number 107 on gadai syariah financing on the existing financing system in Bank Syariah Mandiri. The analysis was performed using descriptive comparative method, which describes and illustrates the gadai syariah financing  on the object of research with SAK 107.As for the object of this research is  Bank Syariah Mandiri, Pontianak branch. Data collection is done by giving interviews and an analysis of financial report.Results from this study indicate that Bank Syariah Mandiri Pontianak has implemented a policy of distribution of gadai syariah financing in accordance with SAK 107, but for the preparation of the financial statements as a whole still has shortcomings. This is because in its financial statements only the balance sheet and income statement in accordance with the guidelines for the preparation of financial report Bank Syariah Mandiri.Keywords: SAK No. 107, Bank Syariah Mandiri Syariah,  Gadai Syariah Financing.